Review: Strategies for enteric methane mitigation in cattle fed tropical forages - Ku-Vera, Juan Carlos; Castelán-Ortega, O.A.; Galindo-Maldonado, F. A.; Arango, Jacobo; Chirinda, Ngonidzashe; Jiménez Ocampo, Rafael; Valencia Salazar, Sara Stephanie; Flores Santiago, E.J.; Montoya Flores, María Denisse; Molina Botero, Isabel Cristina; Piñeiro Vázquez, Ángel Trinidad; Arceo Castillo, Jeyder Israel; et al. (Elsevier, 2020)
Methane (CH4) is a greenhouse gas (GHG) produced and released by eructation to the atmosphere in large volumes by ruminants. Enteric CH4 contributes significantly to global GHG emissions arising from animal agriculture. It has been contended that tropical grasses produce higher emissions of enteric CH4 than temperate grasses, when they are fed to ruminants. A number of experiments have been performed in respiration chambers and head-boxes to assess the enteric CH4 mitigation potential of foliage and pods of tropical plants, as well as nitrates (NO3−) and vegetable oils in practical rations for cattle. On the basis of individual determinations of enteric CH4 carried out in respiration chambers, the average CH4 yield for cattle fed low-quality tropical grasses (>70% ration DM) was 17.0 g CH4/kg DM intake. Results showed that when foliage and ground pods of tropical trees and shrubs were incorporated in cattle rations, methane yield (g CH4/kg DM intake) was decreased by 10% to 25%, depending on plant species and level of intake of the ration. Incorporation of nitrates and vegetable oils in the ration decreased enteric CH4 yield by ∼6% to ∼20%, respectively. Condensed tannins, saponins and starch contained in foliages, pods and seeds of tropical trees and shrubs, as well as nitrates and vegetable oils, can be fed to cattle to mitigate enteric CH4 emissions under smallholder conditions. Strategies for enteric CH4 mitigation in cattle grazing low-quality tropical forages can effectively increase productivity while decreasing enteric CH4 emissions in absolute terms and per unit of product (e.g. meat, milk), thus reducing the contribution of ruminants to GHG emissions and therefore to climate change.